2020
DOI: 10.1097/fbp.0000000000000617
|View full text |Cite
|
Sign up to set email alerts
|

Initial development of a brief assessment of cocaine demand

Abstract: Cocaine demand is a behavioral economic measure assessing drug reward value and motivation to use drug. The purpose of the current study was to develop a brief assessment of cocaine demand (BACD). Results from the BACD were compared with self-report measures of cocaine use. Participants consisted of treatment-seeking individuals with cocaine use disorder (N = 22). Results revealed that indices of brief demand were significantly associated with various self-report measures of cocaine use. Overall, these results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…These results demonstrate the feasibility of a methodology that incorporates behavioral science and brain imaging for assessing cocaine motivational value in the context of a clinical trial. Regarding cocaine demand, the present findings add to the growing number of studies demonstrating the relevance of hypothetical purchasing tasks for assessing demand for psychomotor stimulants such as cocaine (Bruner & Johnson, 2014; Koffarnus et al, 2015; Strickland, Lile, et al, 2016; Yoon, de Dios, Suchting, Vincent, et al, 2021; Yoon et al, 2020; Yoon, Suchting, de Dios, et al, 2021) and methamphetamine (Yoon, Suchting, Cassidy, et al, 2021). Orderliness of the data was notable, with only a single data point from a single participant exhibiting nonsystematicity.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…These results demonstrate the feasibility of a methodology that incorporates behavioral science and brain imaging for assessing cocaine motivational value in the context of a clinical trial. Regarding cocaine demand, the present findings add to the growing number of studies demonstrating the relevance of hypothetical purchasing tasks for assessing demand for psychomotor stimulants such as cocaine (Bruner & Johnson, 2014; Koffarnus et al, 2015; Strickland, Lile, et al, 2016; Yoon, de Dios, Suchting, Vincent, et al, 2021; Yoon et al, 2020; Yoon, Suchting, de Dios, et al, 2021) and methamphetamine (Yoon, Suchting, Cassidy, et al, 2021). Orderliness of the data was notable, with only a single data point from a single participant exhibiting nonsystematicity.…”
Section: Discussionmentioning
confidence: 58%
“…Drug demand is a behavioral economic measure quantifying motivational aspects of a drug (e.g., drug reward value, abuse liability), typically assessed using hypothetical drug purchasing tasks in which individuals are asked how much drug they would purchase and consume as a function of increasing price (Roma et al, 2017). Drug demand is associated with clinically relevant measures of drug use severity (Strickland et al, 2020; Zvorsky et al, 2019) across numerous drugs of abuse, including cocaine (Bruner & Johnson, 2014; Petry, 2000, 2001; Strickland, Lile, et al, 2016; Yoon, de Dios, Suchting, Vincent, et al, 2021; Yoon et al, 2020; Yoon, Suchting, de Dios, et al, 2021). Our group recently observed that baseline cocaine demand predicts treatment response for individuals receiving contingency management for CUD and, importantly, decreases over time as a function of continued abstinence (Yoon et al, 2020; Yoon, Suchting, de Dios, et al, 2021).…”
mentioning
confidence: 99%